Analysis of Financial Report Integrity as a Mediator on Company Value - Letty Risanli, Vio; Safitri, Julia; Yuniarti, Rita (DINASTI RESEARCH, 2025)
Numerous elements impact a company's valuation, with the primary objective being the maximization of profits and the enhancement of the welfare of the company's owners or shareholders. This research aims to investigate the influence of Liquidity and Company Size on Company Value, with Financial Statement Integrity serving as a mediating factor. The study encompasses 25 banking firms listed on the Indonesia Stock Exchange over the period from 2019 to 2023. The independent variables examined are liquidity and company size, while the dependent variable is company value, moderated by Financial Statement Integrity. Data analysis was performed utilizing panel data regression, employing Eviews 9 software. The analysis applied the Random Effect Model method, leading to the formulation of the equation Y = 446.9287 + 11.28726X1 - 8.279071X2 - 0.013080Z. The findings indicate that liquidity positively influences company value, whereas company size and performance do not have a significant impact. Additionally, liquidity does not affect company value when mediated by financial report integrity, nor do company size and performance, and financial report integrity itself does not influence company value.